Optimizing confectionery production: A semi-automatic gummy jelly dropping machine design and performance evaluation - Promjeen, Kanokwan; Phasinam, Thanwamas; Phasinam, Khongdet (Edelweiss Applied Science and Technology, 2024)
Confectionery products, particularly popular among individuals under 17, include treats such as jellies and gummies. Traditionally, the manual process of dropping gummy jelly into molds, one piece at a time, is labor-intensive and time-consuming. This method is susceptible to the gummy jelly’s physical properties, which can coagulate when exposed to air below its melting point. This study presents the development of a semi-automatic gummy jelly dropping machine to streamline the handmade confectionery production process. The machine, fabricated from stainless steel with dimensions of 36.00 centimeters (width) x 56.00 centimeters (height) x 47.00 centimeters (length), utilizes an aluminum piston mechanism (34 millimeters diameter and 142 millimeters length) for controlled gummy jelly dispensing. A 950-watt heater warms the liquid gummy jelly in a basin located at the piston’s back, with tests conducted at temperatures of 80, 100, and 120 degrees Celsius. Results indicate that the optimal temperature for the semi-automatic gummy jelly dropping machine is 120 degrees Celsius, achieving an average dispensing time of 99.35 seconds. The machine’s production capacity is 36.66 kilograms per hour, with a maximum efficacy of 73.75 percent. The produced gummy jelly exhibits a moisture content of 12.07 percent, lightness (L) of 52.63±4.67.63, red/green (a*) of 0.27±0.11, and yellow/blue (b*) of 4.08±3.13. Its hardness measures 1027.75 grams, its gumminess is 916.25 grams, and its water activity (aw) is 0.80. The study is significant since it verifies that there is no microbial development.